2019
DOI: 10.1016/j.materresbull.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth ferrite materials for solar cells: Current status and prospects

Abstract: Different from classical semiconductor photovoltaic devices, for ferroelectric photovoltaic devices, the open-circuit voltage (Voc) can be four and even more orders of magnitude larger than the band gap of the ferroelectric, and the built-in electric field arising from the remnant polarization of the ferroelectric is throughout the bulk region, which is good for obtaining giant power conversion efficiency. Among ferroelectric materials, BiFeO3 with remnant polarization of as high as-100 μC/cm 2 has the narrowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(37 citation statements)
references
References 97 publications
(109 reference statements)
0
36
0
1
Order By: Relevance
“…The same authors reported in 2010 [391] with respect to the in-plane electrodes was found to critically modulate their photovoltaic performances; either, above bandgap voltages (when perpendicular to the current flow) or just enhanced photocurrents (when parallel to the current flow). Following these works, many investigations have been focused on enhancing the photovoltaic properties of BiFeO 3 thinfilms during the last decade, although the overall power conversion efficiency still remains low (below 1%) [393] , [394] , [337,397] , [398] . It has been common to substitute and/or to dope…”
Section: Wide Bandgap Ferroelectric Oxide Thin-filmsmentioning
confidence: 99%
“…The same authors reported in 2010 [391] with respect to the in-plane electrodes was found to critically modulate their photovoltaic performances; either, above bandgap voltages (when perpendicular to the current flow) or just enhanced photocurrents (when parallel to the current flow). Following these works, many investigations have been focused on enhancing the photovoltaic properties of BiFeO 3 thinfilms during the last decade, although the overall power conversion efficiency still remains low (below 1%) [393] , [394] , [337,397] , [398] . It has been common to substitute and/or to dope…”
Section: Wide Bandgap Ferroelectric Oxide Thin-filmsmentioning
confidence: 99%
“…In recent years, the photovoltaic effect of ferroelectric materials, such as Pb(Zr,Ti)O 3 [6], BaTiO 3 [7,8] and BiFeO 3 [9,10,11], have attracted a lot of research for photovoltaic application. Among many ferroelectric materials, BiFeO 3 (BFO) is the most representative [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The calculated bandgap value from Tauc relation are Eg= 2.73 eV and Eg=2.31 eV for compound and composite respectively [38]. The decrease in band gap energy and broad absorption of composite sample makes it more suitable to be used in optoelectronics devices as compared to compound sample [39].…”
Section: Optical Studiesmentioning
confidence: 96%